Identification and expression pattern of a glutathione S‐transferase in Echinochloa crus‐galli. (14th June 2013) - Li, G; Wu, S G; Yu, R X; Cang, T; Chen, L P; Zhao, X P; Cai, L M; Wu, C X
Summary: Plant glutathione S‐transferase (GST) forms a major part of the herbicide detoxification enzyme network in plants. A GST cDNA was isolated from Echinochloa crus‐galli and characterised. The gene, designated EcGST1 ( E. crus‐galli GeneBank no:JX518596 ), has a 684 bp open reading frame predicted to encode a 25 kD protein. Sequence alignment showed that EcGST1 is a GST homologue. Its expression in response to quinclorac treatment was monitored in seedlings (leaves and roots) and adult plants (leaves, roots, stems and seeds) of quinclorac‐resistant (R) and susceptible (S) biotypes of E. crus‐galli . EcGST1 expression was 1.5–3 times greater in the R plants than in the S plants. However, after exposure to quinclorac, the difference in the expression levels of EcGST1 in R plants, compared with S plants, increased to a ratio of 6–10. Enhanced EcGST1 levels should enable greater quinclorac detoxification following quinclorac stimulation in R plants. GST‐based metabolism may be partially responsible for resistance to quinclorac in E. crus‐galli . The results suggest a new resistance mechanism for this R biotype in Chinese rice fields.